2021
DOI: 10.51507/j.jams.2021.14.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as a Complementary Therapy for Cancer Care: Acceptability and Preferences of Patients and Informal Caregivers

Abstract: Background: Acupuncture can effectively manage cancer-related side effects, for both patients undergoing treatment and for cancer survivors. It may also be effective in managing physiological and psychological symptoms common among informal caregivers of cancer patients. Objectives: The aim of this survey was to explore the acceptability and preferences of cancer patients, cancer survivors, and their informal caregivers in relation to acupuncture. Methods: The survey was conducted from 20 th November to 27 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Its side effects are generally mild, such as pain, bleeding or bruising, dizziness, hematoma, and digestive system symptoms [23]. Acupuncture does not interfere with the primary therapy received by patients, but it can be given simultaneously for synergistic results [6,9].…”
Section: Safety and Acceptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Its side effects are generally mild, such as pain, bleeding or bruising, dizziness, hematoma, and digestive system symptoms [23]. Acupuncture does not interfere with the primary therapy received by patients, but it can be given simultaneously for synergistic results [6,9].…”
Section: Safety and Acceptabilitymentioning
confidence: 99%
“…Tack et al [6] researched the reception of patients and caregivers receiving acupuncture therapy for cancer management. Tack found that although not all patients were interested in acupuncture therapy, about 35% of patients wanted to try acupuncture, and about 48% of caregivers were interested in acupuncture.…”
Section: Safety and Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines discuss several mind–body therapies and natural products, with recommendations on acupuncture, reflexology, hypnosis, and massage based on strong evidence [ 10 ]. Our research group previously conducted a survey on the acceptability and preferences of patients and caregivers on acupuncture as a complementary therapy for cancer care at the day clinic of the Kortrijk Cancer Centre [ 11 ]. Furthermore, within our cancer centre, we installed an art therapy programme taking into account the preferences of the patients and their caregivers [ 12 ].…”
Section: Psychosocial Oncology and Complementary Therapiesmentioning
confidence: 99%
“…Numerous studies have demonstrated the effectiveness of complementary practices, including mental techniques (acupuncture) [ 9 ], nutritional interventions (garlic) [ 10 ], and biological methods (ozone and aromatherapy) [ [11] , [12] , [13] ], in promoting healing and overall well-being. The use of TCMP in Turkey was found to be 60.5 % in 2017 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%